Східно-подільська витинанка кін. ХХ - поч.ХХІ ст. Традиції та новаторство - Тихонюк, О. (Інститут народознавства НАН України, 2008)
The article studies the center of Podolsk cut-out. Local and specific qualities of this art form are described. Tracing the genesis of Podolsk cut-out, the influence of traditional folk cut-out’s, modern art events and cultural factors on her evolution. Noted a great role of public events (symposiums, exhibitions, activities of the cut-out museum and specialized circles) in the formation of society.